The Role of Rossby Wave Breaking in Shaping the Equilibrium Atmospheric Circulation Response to North Atlantic Boundary Forcing - Strong, Courtenay; Magnusdottir, Gudrun (Journal of Climate, 2010)
The role of Rossby wave breaking (RWB) is explored in the transient response of an atmospheric general circulation model to boundary forcing by sea ice anomalies related to the North Atlantic Oscillation (NAO). When the NCAR Community Climate Model, version 3, was forced by an exaggerated sea ice extent anomaly corresponding to one arising from a positive NAO, a localized baroclinic response developed and evolved into a larger-scale equivalent barotropic pattern resembling the negative polarity of the NAO. The initial baroclinic response shifted the phase speeds of the dominant eddies away from a critical value equal to the background zonal flow speed, resulting in significant changes in the spatial distribution of RWB. The forcing of the background zonal flow by the changes in RWB accounts for 88% of the temporal pattern of the response and 80% of the spatial pattern of the zonally averaged response. Although results here focus on one experiment, this “RWB critical line mechanism” appears to be relevant to understanding the equilibrium response in a broad class of boundary forcing experiments given increasingly clear connections among the northern annular mode, jet latitude shifts, and RWB.